SCIENTIFIC APPROACHES TO THE DEVELOPMENT OF VOCAL SKILLS IN ADOLESCENT STUDENTS IN MUSIC ART LESSONS IN SECONDARY EDUCATION INSTITUTIONS - Кікавський, І. М.; Василенко, Л. М. (SWorldJournal, 2022)
The article analyzes the scientific approaches that are necessary and appropriate in the process of forming vocal skills in adolescents. The peculiarities of these approaches are covered - holistic, personal, reflexive, strong-willed and creative